2018
DOI: 10.1002/jcp.26895
|View full text |Cite
|
Sign up to set email alerts
|

The effects of expression of different microRNAs on insulin secretion and diabetic nephropathy progression

Abstract: MicroRNAs (miRNAs) have recently become well-known efficacious biomarkers for the diagnosis of diabetic nephropathy (DN). MiRNAs, short noncoding RNAs, are posttranscriptional regulators of gene expression, which regulate several biological cell functions, including insulin production and secretion, as well as insulin resistance in tissues. Today, the focus of the medical world is centered on the role of miRNAs as mediators for different diseases, such as DN and end-stage renal diseases (ESRD). MiRNAs are stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 110 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…Tung et al 19 found that miR-29a is a potential negative regulator of cannabinoid cb1 receptor and inhibits the expression of proinflammatory and profibrogenic mediators, preventing glomeruli damage caused by fibrosis in patients with DM. Mafi et al 20 reported that miR-29b may regulate cytokine-mediated inflammatory processes via the Sp1/NF-jB/miR-29b axis and thus participate in progression of DN. The study by Song et al 21 on miR-29 family members, in 3T3-L1 adipocyte showed that these miR-29 members may play the role of negative regulators in glucose metabolism through miR-29/SPARC (secreted protein acidic and rich in cysteine) signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tung et al 19 found that miR-29a is a potential negative regulator of cannabinoid cb1 receptor and inhibits the expression of proinflammatory and profibrogenic mediators, preventing glomeruli damage caused by fibrosis in patients with DM. Mafi et al 20 reported that miR-29b may regulate cytokine-mediated inflammatory processes via the Sp1/NF-jB/miR-29b axis and thus participate in progression of DN. The study by Song et al 21 on miR-29 family members, in 3T3-L1 adipocyte showed that these miR-29 members may play the role of negative regulators in glucose metabolism through miR-29/SPARC (secreted protein acidic and rich in cysteine) signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Mafi et al. 20 reported that miR-29b may regulate cytokine-mediated inflammatory processes via the Sp1/NF-κB/miR-29b axis and thus participate in progression of DN. The study by Song et al.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are short ncRNAs (∼22 nucleotides) with pivotal effects on the epigenetic modifications of DN [ 17 ]. Meta-analysis has identified that miR-126 and miR-770 could be used as noninvasive biomarkers for DN [ 18 ], and miR-184 could govern renal fibrosis in DN [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are short, noncoding RNAs that could participate in various biological processes by degrading target mRNAs via directly binding to their 3′‐untranslated region (3′‐UTR; Aghabozorg Afjeh & Ghaderian, ; Davis‐Dusenbery & Hata, ; Zhou & Yang, ). The expression profiling of several miRNAs largely correlates with pathological progression of DN, thus many are proposed as diagnostic or therapeutic biomarkers (Kato & Natarajan, ; Mafi, Aghadavod, Mirhosseini, Mobini, & Asemi, ; Wu et al, ). Increasing literatures suggest that miRNAs profoundly involve fibrotic process, of which miR‐24 was shown inhibit fibrosis via directly affecting TGF‐β1/Smad4 pathway (Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%